Spatial Analysis of Environmental Water Quality in Coal Stockpile - Rusdianasari Bow (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
The location of mining is away from the coastline, so the coal stockpiles is needed. Stockpile serves as a temporary dump before the coal is transported through waterways to be marketed locally or abroad. The existence of the stockpiles is could adversely affect the environmental quality regarding air, water, and soil. The monitoring and management of environmental impacts is intended to minimize the impact arising from the existence and operations of coal buildup. The presence of liquid waste that comes from coal stockpile can lower the degree of acidity (pH value) and increase total suspended solid content (TSS), iron (Fe) and manganese (Mn) which when processed will not adversely affect the surrounding environment. The study aimed at mapping the spatial distribution patterns of pollutants in coal stockpile in order to know the quality of environment due to the presence and activity of the coal stockpile. Given the spatial analysis of environmental pollution, the long-term negative impacts due to the presence and the activity of stockpile can be reduced and preventive action can be done. The research begins by determining the coordinates of point samples, water sampling and laboratory analyzes. The results of measurement and analysis in a laboratory are used to make maps of the spatial distribution patterns of environmental quality. Water quality in acid classified stockpile locations around 3.4 with Fe content of 2.34 ppm and Mn content of 1.77 ppm, as well as 406 ppm of total suspended solid.